Preserving Traditional Ecological Knowledge: An Analysis of Cultural Practices and Transmission among Pastoral Nomadic Communities in Cameroon - Song, Kimeng Liberty (Journal of Innovation in Education and Social Research, 2025)
Traditional ecological knowledge (TEK) embodies the understanding and practices that indigenous and local communities have developed over generations concerning their environment. In Cameroon, particularly among pastoral nomadic communities, TEK plays a critical role in managing natural resources and sustaining livelihoods. This study investigates the cultural practices and knowledge transmission processes that sustain Traditional Ecological Knowledge (TEK) among pastoral nomadic communities in the Northwest Region of Cameroon. It explores how these communities maintain, share, and convey their knowledge regarding environmental management, conservation practices, and ecological relationships. Data was collected using qualitative interviews with 30 participants and surveys of 30 participants. Thematic analysis was employed to discern patterns related to TEK preservation and transmission, while survey data were analysed using descriptive and inferential statistics. Findings indicate the significance of cultural practices-such as storytelling, rituals, and apprenticeships-in preserving TEK and supporting biodiversity conservation. This research posits that comprehending these cultural practices is essential for developing effective strategies to facilitate knowledge transmission and ensure the long-term sustainability of pastoral nomadic livelihoods. Thus, it contributes to a deeper understanding of the role of cultural diversity and practices in achieving ecological resilience.